2012
DOI: 10.1590/s0101-31222012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Automated system of seedling image analysis (SVIS) and electrical conductivity to assess sun hemp seed vigor

Abstract: -The development of new procedures for quickly obtaining accurate information on the physiological potential of seed lots is essential for developing quality control programs for the seed industry. In this study, the effectiveness of an automated system of seedling image analysis (Seed Vigor Imaging System -SVIS) in determining the physiological potential of sun hemp seeds and its relationship with electrical conductivity tests, were evaluated. SVIS evaluations were performed three and four days after sowing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 9 publications
0
20
0
14
Order By: Relevance
“…Recentemente, vários trabalhos de pesquisa indicam eficiência do uso de análise computadorizada de plântulas com o sistema SVIS ® na avaliação do vigor de sementes de berinjela (SILVA & CICERO, 2014), trigo (SILVA et al, 2012a), milho doce (ALVARENGA et al, 2012), crotalária (SILVA et al, 2012b), pepino (CHIQUITO et al, 2012), entre outras.…”
Section: Introductionunclassified
“…Recentemente, vários trabalhos de pesquisa indicam eficiência do uso de análise computadorizada de plântulas com o sistema SVIS ® na avaliação do vigor de sementes de berinjela (SILVA & CICERO, 2014), trigo (SILVA et al, 2012a), milho doce (ALVARENGA et al, 2012), crotalária (SILVA et al, 2012b), pepino (CHIQUITO et al, 2012), entre outras.…”
Section: Introductionunclassified
“…It showed that accelerated aging for a period of 48 hours would be appropriate for estimation of storage potential of the seed lots. On assessing seed physiological potential through traditional accelerated aging test, other researchers have also verified reduction on vigor of cotton seeds, during storage, especially under non-controlled environmental conditions (Freitas et al, 2002;Silva et al, 2012); since under such environmental conditions, the seeds are exposed to the fluctuations of temperature and relative humidity, which also contribute to reduction of seed physiological potential. Pourhaadian and Khaajepour (2010) also conducted correlation coefficient and regression relations between seed performance and vigour tests and opined similarly.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers [1,3,4,7,8,9,10,11,12,13,14,17,19,20,21,24,26,27,29,30,32,34,35,36,37,38,41,42,43,44,45,48,49,50,51] have applied image processing for rice germination in their studies. This is because using image processing is rapid, economic, consistent, and objective.…”
Section: Related Workmentioning
confidence: 99%